Isolamento acústico ao ruído da chuva: avaliação em sistemas de coberturas com telhas metálicas - Wittmann, Gabriel (Universidade do Vale do Rio dos Sinos, 2021)
Steel structure roofs have become solutions as a fast and light construction system, serving the most varied types of buildings in the commercial and industrial field. For its sealing, the metallic tile became the main solution for the system as a whole, since its composition of materials allows the combination of extensive service life, mechanical resistance and low thickness that contributes to reaction effects, low overload for the structural system. However, studies indicate that in structures with large spans the rainfall noise can be significantly amplified, resulting in damage to the use of the building and to the well-being of its users. Thus, this work aims to determine the acoustic performance to rainfall sound of roofing systems with metallic tiles, with different compositions. To study this effect on light roofs, using ISO 10140 parameters: parts 1, 3 and 5, a chamber was developed to generate artificial rain and measure the noise caused by the impact on metallic specimens. The samples tested in a simple way and trapezoidal format, were equivalent to the results already published, with impact noise stands in 70 dB, validating the measurement system. By adding a new tile profile, spaced by a structural element and filled with a fibrous core, has reduce the noise caused by the impact of rain in range of 52 dB, thus providing a satisfactory performance, providing a solution for new projects and facilitating the roof retrofit operation existing.
Keywords: Ruído da chuva; ISO 10140; Telha metálica; Retrofit de cobertura; Acústica de edifícios; Rainfall sound; Steel roof; Cover retrofit; Rainfall sound; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo